Isolation, molecular characterization and antibiotic resistant of pathogenic bacteria obtained from raw meat in Dhaka city - Tuly, Nurzahan Yasmin (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.